Erratum to: Work Stress, Organizational Commitment, and Turnover Intention: The Intervening Role of Work Satisfaction - JABM Editorial (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Correction to: Marlapa E, Endri E. 2024. Work Stress, Organizational Commitment, and Turnover Intention: The Intervening Role of Work Satisfaction. Jurnal Aplikasi Bisnis dan Manajemen (JABM), 10(2): 503. https://doi.org/10.17358/jabm.10.2.503 An error appearedin the article entitled “Work Stress, Organizational Commitment, and Turnover Intention: The Intervening Role of Work Satisfaction” published in Jurnal Aplikasi Bisnis dan Manajemen (JABM). In the published article, several punctuation marks and commas were found that were not appropriate, corrections to these errors are as follows: Corrections on page 510:Line 6, Column 1: Should be 96.3%Line 8, Column 1: Should be 0.986Line 12, Column 1: Should be 98.6%Line 28, Column 1: Should be 0.723Line 30, Column 1: Should be Q2Line 32, Column 1: Should be Q2Line 24, Column 2: Should be 20.057 Corrections on page 511:Line 5, Column 1: Should be 6.737Line 7, Column 1: Should be value 0.427 Corrections on page 512:Line 5, Column 1: Should be 10.792Line 15, Column 1: Should be 14.760Line 25, Column 1: Should be 2.473Line 26, Column 1: Should be 0.014 <Line 38, Column 1: Should be 2.234 >Line 39, Column 1: Should be value 0.091Line 51, Column 1: Should be 2.577Line 2, Column 2: Should be 0.125 The original article can be access online at: https://doi.org/10.17358/jabm.10.2.503